Pediatric Colorectal Cancer: A Heterogenous Entity. Issue 2 (March 2020) - Cortez-Pinto, João; Claro, Isabel; Francisco, Inês; Lage, Pedro; Filipe, Bruno; Rodrigues, Paula; Chaves, Paula; Albuquerque, Cristina; Dias Pereira, António
Abstract : Introduction: Colorectal cancer (CRC) is extremely rare in pediatric age. A poor outcome has been reported. Aims: We aimed to characterize a group of pediatric CRC patients. Materials and Methods: All patients with CRC below 18 years old registered in our Familial Cancer Risk Clinic (2002-2016) were included. Clinical and histologic features were evaluated. Germline mutations, microsatellite instability, and DNA mismatch repair proteins expression were analyzed. Results: Five patients were included (3 males; mean age at diagnosis: 14.2 years (range, 9 to 17 y) and 4/5 had family history of cancer in second-degree relatives. With a maximum follow-up of 5.6 years, 2/5 patients died after 10 and 24 months, and 1 recurred after 15 months. All tumors were ≥pT3N2 and 3/5 presented signet ring cells/mucinous histology, corresponding to cases with stronger family history of cancer. Nevertheless, all CRCs analyzed (n=4) were microsatellite stable and/or expressed all mismatch repair proteins. Loss of heterozygosity for the 3 Bethesda dinucleotide markers was detected in 1/3 informative CRCs. A likely pathogenic germline MSH2 mutation was identified in only 1 patient. Conclusions: Pediatric CRC presented advanced disease and poor prognosis. These tumors had distinct histologic and molecular presentations, resembling features from different carcinogenic pathways, thus suggesting a heterogenous nature.